2000
DOI: 10.1046/j.1526-0968.2000.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Plasma Separation

Abstract: Guest Editor's Introduction: This paper was presented at the first plasmapheresis symposium organized by ISAO and the International Center for Artificial Organs and Transplantation on April 3, 1982, Cleveland, Ohio. This paper was printed in the proceedings of this symposium, Plasmapheresis: Therapeutic Applications and New Techniques, edited by Y Nosé and PS Malchesky, JW Smith, and RS Krakauer, Raven Press, New York, 1983, p. 81–92. This paper describes the basic concept of membrane plasma separation. Consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…Solomon and co‐workers (16) found that the filtration velocities prior to the onset of hemolysis were higher than predicted on the basis of deposition theory and the dependence of filtration velocity on wall shear rate was lower than the power 1.5 predicted. Similar findings were noted by Malchesky et al (15) in which the shear rate dependence varied as a function of membrane types:…”
Section: Theoretical Considerations In Membrane Plasma Separationsupporting
confidence: 89%
See 2 more Smart Citations
“…Solomon and co‐workers (16) found that the filtration velocities prior to the onset of hemolysis were higher than predicted on the basis of deposition theory and the dependence of filtration velocity on wall shear rate was lower than the power 1.5 predicted. Similar findings were noted by Malchesky et al (15) in which the shear rate dependence varied as a function of membrane types:…”
Section: Theoretical Considerations In Membrane Plasma Separationsupporting
confidence: 89%
“…Plasma viscosity is a function of the concentration of plasma solutes, particularly that of macromolecules. In the separation of plasmas containing high concentrations of immune complexes, cryoproteins, and total cholesterol, significantly higher transmembrane pressures are encountered, and therefore operation of membrane plasma separators must be carried out at reduced plasma flows (15).…”
Section: Membranes For Plasma Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Operation should be at the lowest possible TMP and generally less than 50 mm Hg. 1,9 In our study, the TMP progressively increased throughout the entire course of plasmapheresis. In the NH group, the TMP remained below the ideal pressure of 50 mm Hg during 59% of the course.…”
Section: Discussionsupporting
confidence: 47%
“…8 For given membrane and module properties, the properties of blood and its concentrations of plasma solutes affect the limits of the filtration process. 9 Regarding the operating conditions during membrane plasmapheresis, Fok et al 5 reported that the vascular access through large veins, smooth blood flow, and constant plasma ultrafiltration flow were the major determinants for development of hemolysis. Our previous study on the hemodynamic effects of the different vascular access sites for DFP revealed that the central vein access group had a higher blood flow rate, a shorter duration of DFP treatment, and a lower dose of heparin.…”
Section: Discussionmentioning
confidence: 99%